Role of Technological Acquisition and R&D Expenditure in Innovative Investment - Weiyu, Zou; Othman, Aniza; Guli, Tang (Frontiers in Psychology, 2022)
Despite the mounting importance of digitalization among industries and the corporate sector, the stress on the transformation of business operations is limited, thus creating a gap in the literature. The current study aims at determining the role of technological acquisition and research and development (R&D) expenditure in innovative investment. Technological acquisition and R&D are two crucial indicators of digital innovation. Therefore, to understand this, the current study collected data using a questionnaire survey method from 341 employees of the R&D department in the corporate sector of China. Data analysis was performed using the structural equation modeling (SEM) technique. The software used for the statistical analysis of the data was Smart-PLS. Results of the study showed a significant relationship between the independent variables (technological acquisition and R&D) and the dependent variables (innovative investment and attitude toward digital innovation). The study also found that attitude toward digital innovation among the employees positively and significantly impacted innovative investment. Moreover, attitude toward digital innovation acts as a partial mediator between technological acquisition and innovative investment, and R&D and innovative investment. Furthermore, technological culture significantly moderated the relationship between technological acquisition and innovative investment, but did not moderate the relationship between R&D and innovative investment. Henceforth, to practically imply the present study, it is important to ensure the use of the technology is made common by providing training to the employees so that the technical skills of the employees can be polished and utilized for the betterment of the firm.